2022
DOI: 10.3354/meps14120
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the role of local and large-scale factors in structuring sandy beach populations: the wedge clam Donax hanleyanus

Abstract: Changes in the structure and dynamics of sandy beach macrofaunal populations result from the simultaneous action of local and regional factors acting synergistically. This is particularly noticeable in transitional interfaces between freshwater and marine ecosystems, where large-scale gradients affect local beach morphodynamics and resident fauna. The wedge clam Donax hanleyanus occurs on beaches with contrasting morphodynamics along the salinity gradient generated by the Rio de la Plata estuary. We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 61 publications
(75 reference statements)
2
3
0
Order By: Relevance
“…interspecific competition, top-down and/or bottom-up processes, or density-dependence at population level) could play a role . In agreement with our findings, Celentano et al (2022) found a higher abundance of wedge clams in dissipative beaches (see Fig. 3e) and an increased relative representation of older adults with higher body size on reflective beaches (see Fig.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…interspecific competition, top-down and/or bottom-up processes, or density-dependence at population level) could play a role . In agreement with our findings, Celentano et al (2022) found a higher abundance of wedge clams in dissipative beaches (see Fig. 3e) and an increased relative representation of older adults with higher body size on reflective beaches (see Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Salinity, followed by chl a and SST, were the most relevant factors that may trigger large-scale differences in wedge clam population attributes, whereas local habitat features (Dean's para meter, grain size, beach slope) played a secondary role. Our observations reinforce regional-scale findings that highlighted salinity as the main factor controlling wedge clam populations in sandy beaches (Celentano et al 2022, Risoli et al 2022.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations